Academic Supervision and Coaching of a Junior Secondary Science Teacher: A Case Study - Budi Prasetyo (Penerbit Goodwood, 2026)
Purpose: This study documents the implementation of academic supervision and post-observation coaching with a Science teacher at a Junior Secondary School (Madrasah Tsanawiyah) in Lampung, Indonesia, examining lesson-plan quality, instructional practice, and assessment implementation as the basis for professional feedback.Research Methodology: A descriptive case-study design was used, combining document analysis of the lesson plan, classroom observation using three structured supervision instruments, and a post-observation coaching session following the GROW model. Each instrument scored multiple indicators on a four-point scale, converted to a percentage-based final result.Results: The lesson-plan instrument yielded 79 out of 96 (82.29%), classified as Good. The lesson-implementation instrument yielded 81 out of 96 (84.38%), also Good. The assessment-implementation instrument yielded 80 out of 96 (83.33%), likewise Good. Coaching interviews indicated that limited textbook availability, rather than instructional skill, was the primary constraint on lesson delivery, and that practicum activities generated strong student engagement despite this constraint.Conclusions: The teacher demonstrated consistently good performance across planning, delivery, and assessment domains, with resource limitation rather than pedagogical weakness identified as the principal barrier.Limitations: The study is based on a single teacher and one supervision cycle, limiting generalizability, and relies on supervisor-administered instruments rather than triangulated multi-rater data.Contributions: The study offers a replicable protocol combining structured observation with GROW-model coaching for supervision practicums, providing benchmark scores for similar academic supervision training in Indonesian teacher education.